Replication of Leafa's Character Outfit in the Sword Art Online Series - Nurizka*, Daiva Naflah; Ruhidawati, Cucu (Riwayat: Educational Journal of History and Humanities, 2023)
The development of the fashion industry is very fast and has intense competition. Every garment must-have function, aesthetics, or uniqueness so that consumers have their interest. One of the garments that is unique and highly creative is creative clothing. Creative Clothing is clothing that is made as a result of someone's creativity, imagination wishful thinking, thoughts, ideas, or inspiration to express creativity. The inspiration or ideas for making these creative clothes can vary, for example, the fantasy genre animated series entitled Sword Art Online. Sword Art Online is a fantasy series that inspired researchers to make creative clothing and the character Leafa in the series became the main idea in making this creative clothing. Leafa is a character from Suguha's sylph race in the Alfheim Online game who helps her older brother, Kirito, to save Asuna who is trapped in the game. This research aims to develop the writer's creativity in making creative clothing and applying the knowledge gained during lectures. This research uses the PPE model method which has three stages, namely planning, production, and evaluation. This research produces creative clothing that suits Leafa's characteristics by selecting shiny fabrics, giving a beautiful and glamorous visual impression. The wing ornaments on this creative clothing also make the clothing more attractive and in line with the concept.